B- and T-Cell Responses After SARS-CoV-2 Vaccination in Patients With Multiple Sclerosis Receiving Disease Modifying Therapies: Immunological Patterns and Clinical Implications - Iannetta, Marco; Landi, Doriana; Cola, Gaia; Campogiani, Laura; Malagnino, Vincenzo; Teti, Elisabetta; Coppola, Luigi; Di Lorenzo, Andrea; Fraboni, Daniela; Buccisano, Francesco; Grelli, Sandro; Mozzani, Marcello; et al. (Frontiers in Immunology, 2022)
Vaccination campaign to contrast the spread of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has raised the issue of vaccine immunogenicity in special populations such as people with multiple sclerosis (PwMS) on highly effective disease modifying treatments (DMTs). While humoral responses to SARS-CoV-2 mRNA vaccines have been well characterized in the general population and in PwMS, very little is known about cell-mediated responses in conferring protection from SARS-CoV-2 infection and severe coronavirus disease-2019 (COVID-19). PwMS on ocrelizumab, fingolimod or natalizumab, vaccinated with two doses of mRNABNT162b2 (Comirnaty®) vaccine were enrolled. Anti-Spike (S) and anti-Nucleoprotein (N) antibody titers, IFN-gamma production upon S and N peptide libraries stimulation, peripheral blood lymphocyte absolute counts were assessed after at least 1 month and within 4 months from vaccine second dose administration. A group of age and sex matched healthy donors (HD) were included as reference group. Statistical analysis was performed using GraphPad Prism 8.2.1. Thirty PwMS and 9 HDs were enrolled. All the patients were negative for anti-N antibody detection, nor reported previous symptoms of COVID-19. Peripheral blood lymphocyte counts were assessed in PwMS showing: (i) reduction of circulating B-lymphocytes in PwMS on ocrelizumab; (ii) reduction of peripheral blood B- and T-lymphocyte absolute counts in PwMS on fingolimod and (iii) normal B- and T-lymphocyte absolute counts with an increase in circulating CD16+CD56+ NK-cells in PwMS on natalizumab. Three patterns of immunological responses were identified in PwMS. In patients on ocrelizumab, anti-S antibody were lacking or reduced, while T-cell responses were normal. In patients on fingolimod both anti-S titers and T-cell mediated responses were impaired. In patients on natalizumab both anti-S titers and T-cell responses were present and comparable to those observed in HD. The evaluation of T-cell responses, anti-S titers and peripheral blood lymphocyte absolute count in PwMS on DMTs can help to better characterize the immunological response after SARS-CoV-2 vaccination. The evaluation of T-cell responses in longitudinal cohorts of PwMS will help to clarify their protective role in preventing SARS-CoV-2 infection and severe COVID-19. The correlation between DMT treatment and immunological responses to SARS-CoV-2 vaccines could help to better evaluate vaccination strategies in PwMS.